2012
DOI: 10.1371/journal.pone.0042056
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Genome of the Free-Living Earwig, Challia fletcheri (Dermaptera: Pygidicranidae) and Phylogeny of Polyneoptera

Abstract: The insect order Dermaptera, belonging to Polyneoptera, includes ∼2,000 extant species, but no dermapteran mitochondrial genome has been sequenced. We sequenced the complete mitochondrial genome of the free-living earwig, Challia fletcheri, compared its genomic features to other available mitochondrial sequences from polyneopterous insects. In addition, the Dermaptera, together with the other known polyneopteran mitochondrial genome sequences (protein coding, ribosomal RNA, and transfer RNA genes), were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 83 publications
(125 reference statements)
2
48
0
Order By: Relevance
“…Some authors agreed on the relative primitive position of the Plecoptera2222367, while the sister relationship between Plecoptera and Dermaptera has been suggested by recent molecular studies1526. In the PhyloBayes tree from the data set of PCGDegenRNA (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Some authors agreed on the relative primitive position of the Plecoptera2222367, while the sister relationship between Plecoptera and Dermaptera has been suggested by recent molecular studies1526. In the PhyloBayes tree from the data set of PCGDegenRNA (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…C. fletcheri ) is available in GenBank. This mitogenome displayed unusual features of strand-bias, and a unique gene arrangement26. With the inclusion of three newly sequenced Dermaptera mitogenome sequences, the long branch of C. fletcheri is shortened, and the whole Dermaptera consistently appears as the earliest divergent lineage of Polyneoptera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ancient nodes that are accepted and corroborated by other data are recovered from mitochondrial data [274,277 -281], and many relationships among polyneopterans are shared between nuclear and mitochondrial analyses [190]. For example, using mtDNA genomes, Wan et al [281] found many of the nodes that Misof et al [50] recovered from transcriptomes (box 4) and some of these nodes (figure 5: P,Q,R) have only rarely been seen before. Mitochondrial data consistently recover Mantophasmatodea with Phasmatodea [273,281].…”
Section: Mitochondrial Genomesmentioning
confidence: 86%
“…This mitogenome was used to generate a phylogram with the following complete mitogenomes of closely related insects: M. arizonensis (KP642637.1), P. princeps (NC 006133.1), Acroneuria hainana (NC 026104.1), Dinocras cephalotes (NC 022843.1), Kamimuria wangi (NC 024033.1), Tamolanica tamolana (NC 007702.1), Ruspolia dubia (NC 009876.1), Sclerophasma paresisense (NC 007701.1), Entoria okinawaensis (NC 014694.1), Blattella bisignata (NC 018549.1), Reticulitermes santonensis (NC 009499.1), and Challia fletcheri (NC 018538.1) (Cameron & Whiting, 2007;Cameron et al, 2006;Chen, 2013;Elbrecht & Leese, 2015;Elbrecht et al, 2013;Huang et al, 2015;Kômoto et al, 2011;Qian et al, 2014;Wan et al, 2012;Zhou et al, 2007). Multiple sequence alignments were performed using ClustalW (Larkin et al, 2007).…”
mentioning
confidence: 99%